1992
DOI: 10.1210/jcem.75.1.1320054
|View full text |Cite
|
Sign up to set email alerts
|

Fetal and maternal endocrine responses to reduced uteroplacental blood flow.

Abstract: In clinical practice, falling or reduced maternal estrogen levels are commonly regarded as indicators of fetal distress. However, experimental studies in primate animal models demonstrate that changes in maternal estradiol concentrations vary in response to reduced uteroplacental blood flow and are elevated during fetal hypoxemic stress, suggesting an increase in fetal adrenal precursor steroids. We studied the effects of graded reductions in maternal distal aortic blood flow (Qda) on the fetal MCR of dehydroe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Alternatively, the growth retardation observed in the stress models may be facilitated via increased sex steroid levels. In subhuman primates, increases in plasma androgen and estrogen metabolites were noted after the induction of hypoxic conditions through arterial ligation, suggesting that fetal and maternal stress have the potential to cause significant increases in sex steroid levels (44). In these studies it is also unclear whether the effects of prenatal T treatment, if any, are due to its androgenic action or are the result of its aromatization to estradiol.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the growth retardation observed in the stress models may be facilitated via increased sex steroid levels. In subhuman primates, increases in plasma androgen and estrogen metabolites were noted after the induction of hypoxic conditions through arterial ligation, suggesting that fetal and maternal stress have the potential to cause significant increases in sex steroid levels (44). In these studies it is also unclear whether the effects of prenatal T treatment, if any, are due to its androgenic action or are the result of its aromatization to estradiol.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to total fetal body weight, they are 20-fold heavier than in the adult 16 . The fetal adrenals respond to stress, such as hypoxemia, by producing more dihydroandrostenedione (DHA), DHA sulfate, and their metabolites 17 . In animal studies, a three-fold increase in adrenal blood flow has been demonstrated during hypoxia 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Adrenal weights of prenatal testosterone-treated female fetuses were clearly larger than controls [25], suggestive of adrenal involvement. Conversely, increases in plasma androgen and estrogen metabolites were noted in subhuman primates following induction of hypoxic conditions through arterial ligation, suggesting that fetal and maternal stress have the potential to cause significant increases in sex steroids [30]. Recent studies have found a positive correlation between fetal plasma testosterone and cortisol in humans [31].…”
Section: Developmental Programming Of Hypertension: Role Of Sex Steroidsmentioning
confidence: 99%